472 INTRAUTERINE GROWTH RESTRICTION ALTERS HEPATIC INSULIN GROWTH FACTOR 1 PROMOTER UTILIZATION AND EXPRESSION. (1st January 2006) - Fu, Q.; McKnight, R. A.; Yu, X.; Callaway, C. W.; Lane, R. H.
Abstract : Background: IUGR predisposes towards lower IGF-1 levels, which is significant because decreased IGF-1 levels contribute to insulin resistance during adulthood. In humans and rats, IGF-1 expression involves the use of different promoters and splice variants. This is a characteristic associated with epigenetic regulation of gene, which is altered in the IUGR liver. IGF-1 expression involves the use of two different promoters, while alternative splicing within exon 4 accounts for the IGF-1 variants A (IGF-1A) and B (IGF-1B). Objective: We therefore hypothesized that IUGR in the rat would influence hepatic expression of IGF-1 and promoter utilization. Methods: IUGR was induced via bilateral uterine artery ligation. Liver was harvested from IUGR and sham controls (Con) on day 0 and day 21. IGF-1 gene expression was measured. Initiation at promoter one (P1) and promoter two (P2) transcription start sites were quantified. Results: Results are expression as percent of Con ± SEM. IUGR decreased IGF-1 protein levels in day 0 IUGR female rats to 52 ± 15%** of Con and decreased IGF-1 protein levels in day 21 IUGR male and female rats to 69 ± 5%** and 29 ± 5%*** of Con values respectively. Similarly, IGF-1A mRNA levels were decreased to 38 ± 2.9%*** and 40 ± 10.3%** of Con in male and female day 0 pups respectively, though no difference was noted at day 21. IGF-1B mRNA levels were decreased to 26 ± 2.3%*** and 39 ± 3.9%*** in male and female day 0 pups respectively. At day 21, IGF-1B mRNA levels were also decreased to 68 ± 6%* and 86 ± 2.9%* of male and female Con levels respectively. At day 0, transcription initiation from P1 in IUGR males and females was 25 ± 2.6%*** and 41 ± 6%*** of Con, with no difference at day 21. Transcription initiation from P2 in day 0 IUGR animals was 39 ± 7%** and 46 ± 2.6%*** in male and females respectively, while at day 21, IUGR still reduced P2 transcription initiation to 75 ± 2.5%*** and 79 ± 4.1%** of male and female control values (* p < .05; **p < .01; ***p < .001). Conclusions: IUGR decreased hepatic IGF-1 gene expression in neonatal and adolescent rats. IGF-1 promoter activity in IUGR from P1 and P2 was decreased at day 0 and P1 remained low at day 21. These findings are novel by demonstrating the effects of IUGR upon IUGF-1 splice variation and promoter utilization. We speculated that IUGR-induced epigenetic reprogramming may play a role in IGF-1 gene expression change using the P2 promoter. March of Dimes and HD41075.